Suburban Coast Salish Inter-Household Co-operation, Economics and Religious Movements - Mooney, Kathleen A. (Culture, 1988)
The Coast Salish Indians studied here have lived with pervasive financial insecurity. Most Indians have coped partly through preaching and practice of a collective ethic of sharing. Some with relatively high earned income have moved in the direction of a more narrow, competitive individualism. Those with social assistance incomes maintain a broad sphere of assistance with kin and community. Families who are strongly committed to Spirit Dancing and the Shaker Church keep alight the most broadly defined generosity towards kin and Indians in need.